Obstetric Study to Exploring the Prevalence and Determinants of Cesarean Sections at Timeragra Teaching Hospital Dir Lower - Wahid, Nazia; Ikram Ullah; Humaira Bibi; Sobia Ali; Arooj Batool; Lubna Islam; Hina Iftikhar (Indus Journal of Bioscience Research, 2025)
Cesarean section (CS) is a pivotal surgical procedure in obstetrics, often performed to manage complications such as dystocia, prior cesarean deliveries, fetal distress, and post-term pregnancies. Despite its importance, the increasing prevalence of CS raises concerns about over medicalization and its associated risks. This study explores the factors influencing CS in District Dir Lower KP, Pakistan, providing insights into demographic, educational, obstetric, and neonatal determinants. Methods: A descriptive cross-sectional study was conducted with a total sample size of 123. Data were collected on variables including maternal age, education level, parity, gestational age, infant size, and gender. Statistical analysis was performed using percentages to identify significant trends and associations. Results: Age Group: Women aged 25-34 years had the highest CS rate (60.97%), followed by those aged ≥35 years (21.14%). Education: Primary education was most prevalent among women undergoing CS (42.28%), while higher education showed the lowest association (7.32%). Parity: Women with three or more children exhibited the highest CS rates (53.66%), whereas first-time mothers accounted for 12.20%. Gestational Age: Normal-term pregnancies (37-40 weeks) had the highest CS prevalence (56.91%), while post-term pregnancies accounted for 14.63%. Baby Size: Average-sized infants (2.5-4 cm) were associated with the highest CS rates (52.85%), compared to small (32.52%) and large infants (14.63%). Infant Gender: Male infants were more commonly associated with CS (62.60%) than female infants (37.40%). Conclusion: This study highlights the significant role of maternal age, education level, parity, gestational age, and infant characteristics in influencing CS rates in District Dir Lower Findings emphasize the need for evidence-based maternal health policies to optimize delivery outcomes and address unnecessary surgical interventions.